2021
DOI: 10.21203/rs.3.rs-842102/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rational Medicine Prescription and Adherence to Prescription Format: A Description of Practices in the Private Sector in Addis Ababa, Ethiopia

Abstract: Background: In Ethiopia, despite the private health sector's role in healthcare delivery is growing, studies on private health sector prescribing practices are uncommon. The main aim of this study was to evaluate the private health sector's rational prescribing practices and adherence to prescription format, using some of the World Health Organization (WHO) core drug use indicators in Addis Ababa, Ethiopia. Method: A retrospective cross sectional study design was used to collect quantitative data from prescrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
1
1
Order By: Relevance
“…With regard to the bacteriological isolation of the milk samples, out of 122 CMT positive samples used for bacteriological culture, 114(93.44%) samples were found culture positive for single or more bacterial species and 8(6.56 %) CMT positive collected milk samples were found culture negative (Table 1). The result of the present study is lower than the report of [20] who reported (9.2%) negative culture, [21] reported 15(10%) and [22] who reported (9.82%) culture negative milk samples. "The failure to isolate bacteria from the CMT positive milk samples could be associated with spontaneous elimination of the infection, low concentration of pathogen in milk, intermittent shedding of pathogen and intracellular location of pathogens and presence of inhibitory substance in milk" [23].…”
Section: Bacteriological Examinationcontrasting
confidence: 91%
“…With regard to the bacteriological isolation of the milk samples, out of 122 CMT positive samples used for bacteriological culture, 114(93.44%) samples were found culture positive for single or more bacterial species and 8(6.56 %) CMT positive collected milk samples were found culture negative (Table 1). The result of the present study is lower than the report of [20] who reported (9.2%) negative culture, [21] reported 15(10%) and [22] who reported (9.82%) culture negative milk samples. "The failure to isolate bacteria from the CMT positive milk samples could be associated with spontaneous elimination of the infection, low concentration of pathogen in milk, intermittent shedding of pathogen and intracellular location of pathogens and presence of inhibitory substance in milk" [23].…”
Section: Bacteriological Examinationcontrasting
confidence: 91%
“…Third, there is also an acute shortage in the global supply of spices with growing demand, which has resulted in higher prices on global markets (Herms, 2015, p. 6). Rwanda's climate and soil conditions are favourable for spice cultivation (Schramm, 2019, p. 6), and Ethiopia has vast amounts of uncultivated land that has been vouched for expanding production of its already thriving spice industry (Mekuria, 2016). However, while Rwanda at the time had a very small spice industry, Ethiopia had a strong existing spice trade, including with India, exporting US$7.8m in 2016, compared to Rwanda's US$0.01m.…”
Section: Supporting Indian Trade and Investment For Africa Interventi...mentioning
confidence: 99%